2020
DOI: 10.1057/s41599-020-0439-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of game genres and gamers’ communication networks in perceived learning

Abstract: The present study examined the educational roles of games that were not designed for pedagogical purposes. With respect to the roles of gamers' communicationcommunication networks, network diversity, and heterogenous discussion-three specific sub-objectives of the present work include: (1) to examine the extent to which games can be social learning environments, (2) to examine how gamers' communication contributes to perceived learning, and (3) to evaluate the relationship between game genre's unique character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Research Question 5: is CC correlated with the awareness of social learning behavioural and cognitive processes?Hypothesis there is a significant correlation between CC and awareness of social learning dynamic (e.g., Jung, 2020a, 2020b). …”
Section: Expanding the Educational Impact Of Video Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research Question 5: is CC correlated with the awareness of social learning behavioural and cognitive processes?Hypothesis there is a significant correlation between CC and awareness of social learning dynamic (e.g., Jung, 2020a, 2020b). …”
Section: Expanding the Educational Impact Of Video Gamesmentioning
confidence: 99%
“…Indeed, preliminary evidence shows that game outlets can be proactive environments where community and educational instances may take place (Gandolfi et al, 2021;Pearce, 2011). Moreover, online gaming and related social engagement have been related to positive and inclusive learning experiences (Jung, 2020a;Squire, 2010), where problem solving and critical thinking are promoted in a shared environment (Hau & Kim, 2011). For instance, Jung (2020aJung ( , 2020b has found that the more players play and interact with others in these outlets, the more they appreciate and harness related dynamics of socialization and community building.…”
Section: Video Games As Transformative Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As advanced digital technology goes, more video games are developed and published to serve many purposes, including communicating with the player. Video game communicates through visual, audio, video, and human interfaces to engage with players, regardless their gender, age, occupation, social class, or even nationality [1]. In this digital era, video games hold important roles as digital media that could be used for several purposes.…”
mentioning
confidence: 99%
“…In this digital era, video games hold important roles as digital media that could be used for several purposes. One of these purposes is as an educational media to share, discuss, and even to criticize several real-life issues and conflicts such as issues in politics, lifestyles, mental health, even as far as human behaviour in a certain community [1]. In its role as an interactive and communicative media, a video game could be as simple as a five-minute duration of gameplay to deliberate such an important topic.…”
mentioning
confidence: 99%